Physical activity in gestational trimesters and perinatal outcomes in SUS puerperal women - Tauana Prestes Schmidt; Talita Tuon; Katia J. Pudla Wagner; Antonio Fernando Boing; Ana Lúcia Danielewicz (Universidade de São Paulo, 2021)
ABSTRACT OBJECTIVE Test the association between the practice of physical activity (PA) according to the gestational trimesters and the occurrence of cesarean delivery, prematurity, and low birth weight in puerperal women assisted in the Unified Health System of Santa Catarina, Brazil. METHODS A cross-sectional study was conducted with a probabilistic sample of puerperal women who gave birth in public maternity hospitals in Santa Catarina from January to August 2019. The cesarean delivery outcome was self-reported, and information on premature birth (< 37 gestational weeks) and low birth weight (< 2,500 grams) were obtained from medical records. The practice of PA during pregnancy and according to each trimester was self-reported. Multivariate Logistic Regression analyses and interviews with 3,580 puerperal women were carried out. RESULTS PA practice during any period of pregnancy was reported by 20.6% of the sample, with a gradual reduction in prevalence according to the gestational trimester (16.2%, 15.4%, and 12.8%). The highest prevalences of outcomes concerning the total sample were observed in puerperal women who did not practice PA in the third trimester, with 43.9% for cesarean delivery, 7.7% for low birth weight, and 5.5% for premature birth. The odds of cesarean delivery (OR = 1.40; 95%CI 1.10-1.76) and low birth weight (OR = 1.99; 95%CI 1.04-3.79) were, respectively, 40% and 99% higher among puerperal women who did not practice PA in the third trimester of pregnancy when compared to those who practiced PA. There was no association between PA practice and prematurity. CONCLUSION Puerperal women who did not practice PA in the third trimester of pregnancy were more likely to have cesarean delivery and low birth weight newborns.